Evaluation of three commercial kits effective identification of menstrual blood based on the D-dimer. (September 2022) - Tsai, Li-Chin; Liu, Kuo-Lan; Lin, Wan-Ying; Lin, Yu-Chih; Huang, Nu-En; Lee, James Chun-I.; Linacre, Adrian; Hsieh, Hsing-Mei
Abstract: Blood or bloodstains are encountered frequently in forensic investigations. Presumptive and more confirmatory tests for peripheral blood are well established, however, similar methods for menstrual blood identification are less so. D -dimer is a fibrin degradation product that occurs at high concentration in menstrual blood and therefore a potential target to screen for this body fluid. We evaluated three rapid tests to determine if they can discriminate menstrual blood from peripheral remote from a laboratory setting. Their sensitivity, specificity and robustness were also assessed. The assays were: a latex agglutination (Dade Dimertest Latex Assay), SERATEC PMB test and OneStep D -dimer RapidCard InstaTest, both of which are based on lateral flow immunochromatographic analysis. Of the three, greater sensitivity was observed using the OneStep D -dimer RapidCard InstaTest, regardless of whether liquid or a stain was used. This test also detected a result using the smallest volume of menstrual blood, 0.003125 μL. Specificity testing was based on six different body fluids (urine, saliva, peripheral blood, semen, sweats and vaginal fluid) resulting in all 30 samples testing negative for the D -dimer using the OneStep D -dimer RapidCard InstaTest. Mixtures at ratios 1:1, 1:3 and 1:9 (menstrual blood: the other biofluid or PBS) were tested and the results showed that D -dimer could be detected for all samples using either the Dade Dimertest Latex Assay or the OneStep D -dimer RapidCard InstaTest. The body fluids were exposed to environmental stresses such as various temperature (−20 °C, 4 °C, room temperature and 37 °C for 30, 90, 180 and 360 days) and fluctuations in humidity (42%, 76% and 100% humidity at room temperature for 1, 3, 5, 10 and 20 days): all samples were D -dimer positive using the OneStep D -dimer RapidCard InstaTest though the strength decreased relative to the increase of storage time and temperature or humidity. All 6 postmortem blood samples gave a positive result for D -dimer using the OneStep D -dimer RapidCard InstaTest and 2 samples gave a positive response using the Dade Dimertest Latex Assay and the SERATEC PMB test; peripheral blood postmortem samples can show an increase in D -dimer. Menstrual blood was recovered from the pads under the sample wells after testing using the two immunochromatographic assays from which STR alleles could be amplified successfully. The results presented here support the application of these commercial kits for effective identification of menstrual blood. Graphical Abstract: ga1 Highlights: Three commercial kits for D-dimer tests were evaluated for their applications on forensic menstrual blood identification. All these three kits showed high sensitivity and specificity, and minimally influenced by the environmental stresses. Peripheral blood postmortem samples showed an increase in D -dimer. The menstrual blood recovered from the pads after completion of the immunochromatographic assays generated full STR profiles.